Screening and Characteristics Analysis of Polysaccharides from Orah Mandarin (Citrus reticulata cv. Orah) - Guoming Liu; Ping Wei; Yayuan Tang; Jiemin Li; Ping Yi; Zhonglin Deng; Xuemei He; Dongning Ling; Jian Sun; Lan Zhang (Foods, 2023)
This study aimed to screen out polysaccharides with the ability to activate NK cells. Ten polysaccharides (OP) were isolated from orah mandarin (Citrus reticulata cv. Orah) peel using hot-water extraction combined with the alcohol precipitation method and the ultrafiltration-membrane separation method. After measuring the effects of 10 OPs on NK-92MI cell proliferation and cytotoxicity, it was found that the polysaccharide OP5 had the highest activity in vitro. OP5 can significantly promote the proliferation of and increase the gene expression of perforin, granzyme B and IFN-γ in NK-92MI cells. Its molecular weight was between 50 and 70 kDa. The identification results of monosaccharide composition indicated that OP5 was composed of arabinose (31.52%), galacturonic acid (22.35%), galactose (16.72%), glucose (15.95%), mannose (7.67%), rhamnose (2.39%), fucose (1.41%), xylose (1.30%), glucuronic acid (0.42%) and ribose (0.27%). The sugar ring of the β-configuration was the main, and that of the α-configuration was the auxiliary. These results would provide a foundation for the functional product development of OPs.